The Association between Obesity-Risk Genes and Gestational Weight Gain Is Modified by Dietary Intake in African American Women. (1st March 2018) - Meng, Ying; Groth, Susan W.; Li, Dongmei
Abstract : Obesity-risk genes have been associated with dietary intake, appetite regulation, and gestational weight gain (GWG). The purpose of this study was to examine whether dietary intake including total energy intake and macronutrients modify or mediate the association between obesity-risk genes and GWG. An observational study was conducted with 85 African American pregnant women. Sociodemographic, medical, and lifestyle factors and dietary recalls were collected during pregnancy. Seven obesity-risk genetic variants were genotyped. Regression analyses with bootstrapping methods were used to examine the moderation and mediation effects of dietary intake. The mean GWG was 14.2 kg, and 55.3% of the women gained above the Institute of Medicine GWG guidelines. A nominally significant association was found between rs17782313 (close to MC4R ) and percentage of energy intake from fatP = 0.043 . A variant downstream of KCTD15 (rs11084753) was nominally significantly related to GWGP = 0.023 . There was a significant interaction between the KCTD15 polymorphism and dietary fat intakeP = 0.048 . Women with the AG genotype gained more weight during pregnancy with more dietary fat consumption. In conclusion, our results indicate that dietary macronutrients, especially fat intake, may modify the effect of the KCTD15 gene on GWG. Improved knowledge of gene-diet interactions can facilitate the development of personalized interventions.